Urban Tapestry: A Place-Sensitive Approach to Sustainable Urban Design - Noor Hasharina Hassan; Gabriel Yit Vui Yong; Izni Azrein Noor Azalie; Norzurianie Kamarulzaman (International Journal of Environment, Architecture, and Societies, 2022)
Shophouses are essential elements of the urbanscape. However, the rate at which they are developed and neglected in Brunei has given rise to various problems in commercial areas, which undermines sustainability. While commercial areas are places with unique characteristics created as a consequence of the interaction between people and the environment, they tend to be inconspicuous to outsiders, including authorities and planners. This paper proposes a way to elucidate the genius loci of a site using urban tapestry as an analytical model rather than just a metaphor. The Menglait commercial area (MCA) was used as a case to illustrate this method. The MCA tapestry depicts a place for the common people to fix their automobile issues and quick social-business meet-ups. Its threads could be traced to the area’s early development, interweaving national development programs with the introduction of the automobile, the Chinese diaspora, and the development of the oil industry. Traditionally, shophouses, which were functional and ecological in design, have become wasteful in their modern form due to changing urban realities. Concerning the MCA, its apparent decline could be revealed through the tapestry method. Planned rejuvenation of the area would have obliterated existing features, structures, and knowledge that have essential values to enhance its resilience as a commercial area. The utility of our tapestry method is in the conservation of the genius loci of an area when integrated into the standard urban planning process.